2022
DOI: 10.3390/mi13060927
|View full text |Cite
|
Sign up to set email alerts
|

Motor Imagery EEG Classification Based on Transfer Learning and Multi-Scale Convolution Network

Abstract: For the successful application of brain-computer interface (BCI) systems, accurate recognition of electroencephalography (EEG) signals is one of the core issues. To solve the differences in individual EEG signals and the problem of less EEG data in classification and recognition, an attention mechanism-based multi-scale convolution network was designed; the transfer learning data alignment algorithm was then introduced to explore the application of transfer learning for analyzing motor imagery EEG signals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“… Accuracy comparison of different methods on the BCI competition IV dataset 2a. Each label on the vertical axis represents a method in a study, which is from Gaur et al ( 2021 ); Lashgari et al ( 2021 ); Lian et al ( 2021 ); Liu and Yang ( 2021 ); Liu et al ( 2021 ); Qi et al ( 2021 ); Ali et al ( 2022 ); Ayoobi and Sadeghian ( 2022 ); Chang et al ( 2022 ); Chen L. et al ( 2022 ); Ko et al ( 2022 ); Li and Sun ( 2022 ); Li H. et al ( 2022 ), and Tang et al ( 2022 ), from top to bottom, respectively. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Accuracy comparison of different methods on the BCI competition IV dataset 2a. Each label on the vertical axis represents a method in a study, which is from Gaur et al ( 2021 ); Lashgari et al ( 2021 ); Lian et al ( 2021 ); Liu and Yang ( 2021 ); Liu et al ( 2021 ); Qi et al ( 2021 ); Ali et al ( 2022 ); Ayoobi and Sadeghian ( 2022 ); Chang et al ( 2022 ); Chen L. et al ( 2022 ); Ko et al ( 2022 ); Li and Sun ( 2022 ); Li H. et al ( 2022 ), and Tang et al ( 2022 ), from top to bottom, respectively. …”
Section: Resultsmentioning
confidence: 99%
“…A detailed table with information on the directions and performance of each paper can be found in the Supplementary material . The following reviewed papers are presented in ascending order of their published date (Aellen et al, 2021 ; Asheri et al, 2021 ; Ashwini and Nagaraj, 2021 ; Awais et al, 2021 ; Cai et al, 2021 ; Dagdevir and Tokmakci, 2021 ; De Venuto and Mezzina, 2021 ; Du et al, 2021 ; Fan et al, 2021 , 2022 ; Ferracuti et al, 2021 ; Gao N. et al, 2021 ; Gao Z. et al, 2021 ; Gaur et al, 2021 ; Lashgari et al, 2021 ; Lian et al, 2021 ; Liu and Jin, 2021 ; Liu and Yang, 2021 ; Liu et al, 2021 ; Qi et al, 2021 ; Rashid et al, 2021 ; Sun et al, 2021 ; Varsehi and Firoozabadi, 2021 ; Vega et al, 2021 ; Vorontsova et al, 2021 ; Wahid and Tafreshi, 2021 ; Wang and Quan, 2021 ; Xu C. et al, 2021 ; Xu F. et al, 2021 ; Yin et al, 2021 ; Zhang K. et al, 2021 ; Zhang Y. et al, 2021 ; Algarni et al, 2022 ; Ali et al, 2022 ; Asadzadeh et al, 2022 ; Ayoobi and Sadeghian, 2022 ; Bagchi and Bathula, 2022 ; Chang et al, 2022 ; Chen J. et al, 2022 ; Chen L. et al, 2022 ; Cui et al, 2022 ; Geng et al, 2022 ; Islam et al, 2022 ; Jia et al, 2022 ; Kim et al, 2022 ; Ko et al, 2022 ; Li and Sun, 2022 ; Li H. et al, 2022 ; Lin et al, 2022 ; Li Q. et al, 2022 ; Lu et al, 2022 ; Ma et al, 2022 ; Mattioli et al, 2022 ;...…”
Section: Search Methods and Reviewed Tablementioning
confidence: 99%
“…For instance, it is demonstrated that CNNs are effective in terms of both decoding and visualising EEG signals, and are able to automatically learn spatial features from raw EEG data through convolutional and pooling layers, enabling accurate classification of different action categories [2]. It is also proven that employing a multiscale CNN architecture to capture both frequency and temporal information from EEG signals can lead to improved classification accuracy [3].…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…Initially, the random weights are selected for the input to the hidden layer and the hidden to the output layer in an ANN model. Error (Er) is calculated by comparing the calculated output denoted as C Cal i and the average of the input parameters termed as C Avg i for each parameter, as shown in Equation (11). By adjusting the weights itself, the error is minimized in each iteration.…”
Section: Update the Velocity Vector (αmentioning
confidence: 99%
“…Currently, the artificial intelligence (AI) technique is utilized for healthcare data analysis especially for the cardiogenic issues [10]. The machine mimics the way a human observes, interprets, evaluates, and makes decisions based on the trained data [11]. Powered with multiple supervised and unsupervised learnable algorithms, AI replaces traditional rule-based strategies with data-driven approaches and is capable of learning from the positive and negative experiences.…”
Section: Introductionmentioning
confidence: 99%